Evaluation of Organoleptic Acceptability, Lactic Acid Bacteria Content, and Nutritional Composition of Purple Sweet Potato Yogurt - Vanessa, Nuke; Yenni Okfrianti; Yulianti, Risda (Universitas Airlangga, 2026)
Yogurt is a fermented dairy beverage made primarily from cow's milk as the main ingredient. The addition of purple sweet potato extract filtrate can provide color and increase the nutritional content of yogurt while enhancing consumer acceptance. This study aims to evaluate organoleptic acceptability and analyze the presence of Lactic Acid Bacteria (LAB), protein content, fat content, and water content in yogurt enriched with purple sweet potato extract filtrate. This study is an experimental study using a completely randomized design (CRD) with one factor. The factor applied was the addition of purple sweet potato extract filtrate (Ipomoea batatas) with treatment units F0 0%, F1 5%, F2 10% and F3 15%. Data were obtained from organoleptic tests of color, aroma, taste, viscosity and overall acceptability by 30 trained panelists. The results of the organoleptic test showed that F3 was the most preferred yogurt formulation with the addition of 15% purple sweet potato extract filtrate. Total Lactic Acid Bacteria (LAB) in F3 was 2.47 x 108cfu/ml, protein content in yogurt with the addition of purple sweet potato (Ipomoea batatas) extract filtrate (F3) was 0.48%, fat content in yogurt with the addition of purple sweet potato (Ipomoea batatas) extract filtrate (F3) was 0.20% and water content was 82.92%. The F3 product can be classified as a probiotic product based on LAB content, however it needs modification to increase protein and fat content in accordance with SNI 2891-2009 standards.